Size-selective molecular recognition based on a confined DNA molecular sieve using cavity-tunable framework nucleic acids - Xiaoyi Fu (Nature Portfolio, 2020)
Size-selective discrimination is an issue in biosensing. Here, the authors report on a size selective DNA nanocage which excludes agents based on size and protects the probes against degradation, and demonstrate the discrimination between mature and precursor miRNA.